THE IMPROVEMENT STUDENT’S SPEAKING SKILL IN ENGLISH LESSON WITH ACTION LEARNING STRATEGY IN FIFTH GRADE OF ELEMENTARY SCHOOL 106162 MEDAN ESTATE - EVA BETTY SIMANJUNTAK (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2014)
ABSTRACTThis study deals with the improvement student’s speaking skill in english lesson with action learning strategy in fifth grade of elementary school No106162 Medan Estate. This study was conducted by using classroom  action research. The subject of the research was class V elementary school No106162 Medan Estate. 054914  that consisted of 35 students. Data collected  through the observation perform  test on student speaking skill in the form of an oral test.  The improvement also can be seen from the percentage of the students speaking achievement. In the initial test only 14,2% (five students) got category skill. In the post test in cycle I and cycle II 45,71% (sixteen students) and 88,57% (thirty one students) got category skill. It means theer was an improvement about 74,37. It can  be concluded that there was a significant effect of moving toward better by using action learning strategy to improve students speaking skill. Key word: action learning strategy, english lesson.